Effects of Molybdenum Supplementation in the Form of Ammonium and Sodium Salts on Trophoblast Cell Physiology and Gene Expression In Vitro - Vladimira Foteva; Joshua J. Fisher; Yixue Qiao; Roger Smith (Journal of Developmental Biology)
Molybdenum is an essential trace element sourced during pregnancy from the maternal diet. Studies regarding molybdenum have primarily focused on overexposure in animal and cell culture studies. The effects of molybdenum supplementation on placental function are unknown. An immortalised trophoblast cell line was used to examine the placental cellular response to molybdenum in its bioavailable form as molybdate. Cells of the extravillous trophoblast first-trimester cell line HTR8-SVneo were cultured in complete cell media in the presence of 10 nM to 1 mM of ammonium molybdate or sodium molybdate. Following the addition of the molybdate salts, cell growth, viability, and several gene pathways were monitored. Sodium molybdate salt in doses from 10 nM to 1 mM did not affect cell growth or viability. Exposure to ammonium molybdate at a 1 mM concentration significantly decreased cell growth and viability (p < 0.05). Gene pathways involving molybdoenzyme expression, molybdenum cofactor synthesis, antioxidant response, and angiogenesis were affected following supplementation, although these effects differed depending on the dose and molybdate salt utilised. Molybdoenzyme activity was not affected by supplementation in a dose-dependent manner. The results indicate sodium molybdate is a more appropriate salt to use in vitro, as ammonium molybdate exposure reduced cell viability and growth and downregulated the expression of antioxidant genes NFE2L2 (p < 0.01), SOD1 (p < 0.001) and SOD2 (p < 0.001), suggestive of an inflammatory response. Sodium molybdate affected gene, protein, and activity levels of molybdoenzyme, antioxidant, and angiogenic molecules in vitro. This work demonstrates that sodium molybdate supplementation has pleiotropic effects in vitro and is well tolerated by placental cells at a range of nanomolar and micromolar concentrations.